Evaluation of contact toxicity of new insecticides against egg parasitoid, Trichogramma chilonis - ., Shahanaz; Rahman, S J; ., Shahanaz (Indian Journal of Plant Protection, 2020)
The contact toxic effect of commonly used new insecticides viz., indoxacarb, thiodicarb, spinosad, and endosulfan at recommended concentrations was tested for the egg parasitoid, Trichogramma chilonis under laboratory and greenhouse conditions. All the test insecticides were toxic at 24 h after treatment. Spinosad proved to be highly toxic in terms of adult mortality at 24 h. Under laboratory conditions adult emergence was significantly lesser in test insecticides as compared to control when tricho cards were exposed to treated potted plants. Spinosad proved to be more toxic with least adult emergence (37.4%) when tricho cards were sprayed along with potted plants under green house conditions.